HOW DOES CHANGING SEATING ARRANGEMENTS AFFECT STUDENTS’ ATTENTION AND PARTICIPATION? - Mansurovna, Sohibova Zarnigor (Research Focus International Scientific Journal, 2026)
In recent years, classroom seating arrangements have become an important factor in improving students’ learning and engagement. However, students who sit in the back rows often tend to talk to each other and lose attention during lessons, which reduces their participation in classroom activities. This study aims to examine the relationship between seating arrangements and students’ attention and participation, as well as to identify the most suitable seating arrangement for primary school learners. To explore this, different seating arrangements including U-shaped seating and other classroom layouts, were implemented. The research employed a survey-based approach and was conducted with 15 fourth-grade students at School No. 20 in the Fergana region. Data were collected through student questionnaires to identify their opinions about the current seating arrangement, as well as through classroom observations to better understand how different seating styles affect students’ attention and participation. The findings indicate that changing seating arrangements can significantly increase students’ activity and attentiveness during lessons. These results suggest that flexible seating arrangements may help teachers create a more interactive and effective learning environment, ultimately improving students’ attention and participation.